Case Report: Acute Heart Failure Induced by the Combination of Takayasu's, Takotsubo and Coronary Vasospasm in an Elementary School Teacher–A Reaction to Return-to-Work Stress After COVID-19? - Pires, Inês; Mapelli, Massimo; Amelotti, Nicola; Salvioni, Elisabetta; Ferrari, Cristina; Baggiano, Andrea; Conte, Edoardo; Mattavelli, Irene; Agostoni, Piergiuseppe (Frontiers in Psychiatry, 2022)
Introduction: Takayasu’s arteritis (TA) is a systemic inflammatory disease that affects aorta and its major branches. There are several cardiac manifestations of TA, namely Takotsubo syndrome (TTS). The role of emotional stress in this context is unknown. Case presentation: A 58-year-old Caucasian female elementary school teacher, with history of generalized anxiety disorder (GAD), severe asymptomatic aortic regurgitation (AR) and TA was admitted in the emergency department with chest pain and dyspnea, initiated after a period of intense emotional stress (increased workload during COVID-19 pandemic). Physical examination revealed signs of heart failure (HF) and an early diastolic heart murmur. The electrocardiogram showed sinus tachycardia, T wave inversion in left precordial and lateral leads, and prolonged QTc interval. Laboratorial evaluation presented elevation of high-sensitivity troponin I and B-type natriuretic peptide. The transthoracic echocardiogram revealed severe dilation of left ventricle (LV) with moderate systolic dysfunction, due to apical and midventricular akinesia, and severe AR. The coronary angiography showed normal coronary arteries. An acetylcholine provocative test induced spasm of the left coronary artery, accompanied by chest pain and ST depression, completely reverted after intracoronary nitrates administration. The patient was switched to diltiazem and a drug multitherapy for HF was started. A cardiac magnetic resonance revealed improvement of ejection fraction to 53%, signs of myocardial edema and increased extracellular volume in apical and mid-ventricular walls, and absence of myocardial late gadolinium enhancement. A final diagnosis was myocardial infarction with nonobstructive coronary arteries due to TTS and coronary vasospasm in a patient with GAD and TA. Discussion: We present the first case of acute HF showing coexistence of TA, TTS and coronary vasospasm. TA is a rare inflammatory disease that can be associated with TTS and coronary vasospasm. Furthermore, coronary vasospasm may also be involved in TTS pathophysiology, suggesting a complex interplay between these diseases. Mood disorders and anxiety influence the response to stress, through a gain of the hypothalamic-pituitary-adrenal axis and an increased cardiovascular system sensitivity to catecholamines. Although the mechanisms behind these three pathologies are not yet fully studied, this case supports the role of inflammatory and psychiatric diseases in TTS and coronary vasospasm.